Microevolution in lower Central America: Genetic characterization of the Chibcha-speaking groups of Costa Rica and Panama, and a consensus taxonomy based on genetic and linguistic affinity - Barrantes Mesén, Ramiro (1990)
artículo -- Universidad de Costa Rica, Instituto de Investigaciones en Salud, 1990